Heartbreakers or Healers? Innate Lymphoid Cells in Cardiovascular Disease and Obesity - Roberts, Luke B.; Lord, Graham M.; Howard, Jane K. (Frontiers in Immunology, 2022)
Cardiovascular diseases (CVDs) are responsible for most pre-mature deaths worldwide, contributing significantly to the global burden of disease and its associated costs to individuals and healthcare systems. Obesity and associated metabolic inflammation underlie development of several major health conditions which act as direct risk factors for development of CVDs. Immune system responses contribute greatly to CVD development and progression, as well as disease resolution. Innate lymphoid cells (ILCs) are a family of helper-like and cytotoxic lymphocytes, typically enriched at barrier sites such as the skin, lung, and gastrointestinal tract. However, recent studies indicate that most solid organs and tissues are home to resident populations of ILCs - including those of the cardiovascular system. Despite their relative rarity, ILCs contribute to many important biological effects during health, whilst promoting inflammatory responses during tissue damage and disease. This mini review will discuss the evidence for pathological and protective roles of ILCs in CVD, and its associated risk factor, obesity.